AN EFFECTIVE WAY TO DISPOSE OF RAILWAY FUEL WASTE - Abror Maksimovich Khakimov; Batirjon Takhirovich Khalilaev; Mukhtorbek Rokhimovich Yusupov (Web of Journals Publishing, 2024)
The article discusses some issues related to the utilization of solid waste from railway transport.